Marine Bioremediation Using Alcanivorax Borkumensis SK2 as A Waste Prevention Oil Industry on the Tunda Island to the Impact of Flood in Banten Region - Ilhami, Muhamad Aris; Holifah, Holifah (GMPI Conference Series, 2022)
Marine pollution in the water triggers many problems, one of them is in the area of Tunda Island, Banten, Indonesia. Waste pollution that occurs in the area occurs due to oil drilling activities conducted by Pertamina. As result, such drilling waste pollutes the environment of Tunda Island. The distance between residential areas and oil rigs is about 18 to 20 miles, which will take 2 hours to complete. As a result of the waste, many octopuses on Tunda Island were found drunk and dead. It will be more dangerous if the waste sticks to mangrove seedlings, in mangrove trunks and in seagrass beds, when exposed to sunlight it will melt because the gravel waste is pitch black and can burn. As the world's largest island nation, 60% of Indonesia's 265 million people depend on one-system waters. Toxic chemicals enter the oceans every day from industrial waste. This problem can lead to the risk of flood impacts for the environment affected by industrial waste pollution. Marine cleanliness plays an important role in realizing the prosperity of land and marine ecosystems. Efforts can be made with bioremediation that is recovery with the help of live bacteria such as  Alcanivorax borkumensis  SK2  which is γ-proteobacterium of the sea that can be used to clean contaminated environments. This research aims to prevent industrial waste pollution and prevent the risk of flood impacts in Indonesia, especially in Tunda Island, Banten. Various literature explains that  A. borkumensis  SK2  is able to digest linear and branched alkanes commonly found in crude oil. Bacteria grow naturally in polluted areas, when added with inorganic nitrogen and phosphorus, they can accelerate the cleaning process to 2 -5 years faster than natural processes for 5 - 10 years. Therefore, the application of the use of  A. borkumensis  SK2  has the potential to be applied in Indonesia to overcome the problem of marine pollution.